Long Noncoding RNA SNHG12 Promotes Gastric Cancer Proliferation by Binding to HuR and Stabilizing YWHAZ Expression Through the AKT/GSK-3β Pathway - Zhang, Tianqi; Beeharry, Maneesh Kumarsing; Zheng, Yanan; Wang, Zhenqiang; Li, Jianfang; Zhu, Zhenggang; Li, Chen (Frontiers in Oncology, 2021)
Background: Gastric cancer (GC) is a malignancy with high morbidity and mortality rates worldwide. SNHG12 is a long noncoding RNA (lncRNA) commonly involved many types of cancers in the contexts of tumorigenesis, migration and drug resistance. Nevertheless, its role in GC proliferation is poorly understood. Methods: Bioinformatics and qRT-PCR assays were used to analyze the expression of SNHG12 in GC tissues and cells. In vitro and in vivo experiments were conducted to detect the role of SNHG12 in GC development. qRT-PCR, PCR, western blotting (WB), RNA binding protein immunoprecipitation (RIP), immunoprecipitation (IP), immunohistochemistry (IHC), fluorescence in situ hybridization (FISH) and in situ hybridization (ISH) were performed to investigate the underlying mechanisms by which SNHG12 promotes GC proliferation. Results: SNHG12 was highly expressed in GC cells and tissues, and predicted poor survival. In vitro and in vivo assays showed that SNHG12 knockdown inhibited GC proliferation, while SNHG12 overexpression promoted GC proliferation. Further experiments confirmed that SNHG12 was mainly located in the cytoplasm and bound to HuR. Bioinformatics analysis predicted that YWHAZ was the common target of SNHG12 and HuR, and that the “SNHG12-HuR” complex enhanced the stability of YWHAZ mRNA. Furthermore, YWHAZ, which was highly expressed in GC, predicted poor survival and promoted GC proliferation by phosphorylating AKT. Rescue assays verified that SNHG12 promoted GC proliferation by activating the AKT/GSK-3β pathway. Conclusions: SNHG12 binds to HuR and stabilizes YWHAZ. SNHG12 promotes GC proliferation via modulation of the YWHAZ/AKT/GSK-3β axis in vitro and in vivo. Thus, SNHG12 could become a novel therapeutic target for anti-tumor therapy.